Application of Norm-Referenced Assessment at Vocational High School - Syahrayni, Nurul; Masruhani, Hasna'i; Lumbu, Supriansyah; Urrahmah, Nisa (Nurul Jadid University, 2023)
Assessment is a critical component of the educational process, serving as a means of evaluating student learning and ensuring the overall quality and continuity of instruction. Two major approaches commonly used in educational assessment are norm-referenced assessment (NRA) and criterion-referenced assessment (CRA). This study aims to investigate the implementation of norm-referenced assessment in the context of Arabic language instruction at SMK Muhammadiyah 2 Malang, Indonesia. Employing a qualitative research design, the study utilized the Miles and Huberman interactive model for data collection and analysis. The participants consisted of 12th-grade students and Arabic language teachers. The findings reveal that although teachers are generally familiar with the concept of NRA, both norm-referenced and criterion-referenced assessment approaches have not been explicitly or systematically applied in the classroom. These results suggest the need for increased awareness and training in assessment methodologies to improve instructional effectiveness and student evaluation.ied in this class.